Cultural Shock Among African Students in Indonesia - Astelia Mihayo (ELS Journal on Interdisciplinary Studies in Humanities, 2019)
This paper explores cultural shock experiences encountered by African students studying in Indonesian Universities. The study used qualitative approach to collect data through in-depth face-to-face interviews with African students and participant observation. The findings of the study reveal that many African students had experienced unfamiliar situation that are different from those of their home countries in the course of study in Indonesia. Such situation leads to what is called “culture shock”, which includes new academic life, culture fatigue, language barrier and food outlets. The study has shown that most of the stress had a profound impact on shaping their acculturation and living in Indonesia. The study adds knowledge to literature, particularly on generating ideas for better management of culture shock in an alien environment. Accordingly, the study recommends that before embarking to abroad for education, it is very important to understand the mechanism and consequences of study abroad and shape our knowledge of how these experience function worldwide and students should develop positive attitudes in order to ease their adjustment to an alien culture and setting.